A Bibliometric Analysis of Primary Aldosteronism Research From 2000 to 2020 - Wang, Chengyuan; Jing, Hongwei; Sun, Zuyu; Yao, Jiaxi; Zhang, Xinyu; Liu, Tao; Wu, Ying (Frontiers in Endocrinology, 2021)
Thousands of papers on primary aldosteronism (PA) have been published in the last two decades. This study aimed to evaluate the research hotspots and future trends in PA research using bibliometric analysis. A total of 2365 PA research papers between 2000 and 2020 were included. The dominant position of the United States in global PA research throughout this 20-year period was evident, and it was also the country most frequently involved in international cooperation. The University of Padua was the most productive institution and a leader in research collaboration. Journal of Clinical Endocrinology & Metabolism was the most productive journal in terms of the number of publications on PA. Further, Mulatero P, Reincke M, Beuschlein F and Wu VC all made significant contributions to PA research. Five hotspots have been identified: (1) metabolic syndrome associated with PA; (2) molecular mechanisms of PA; (3) adrenal adenoma and adrenal cortex; (4) hypertension associated with PA; and (5) clinical monitoring parameters and diagnosis in patients with PA. Our results suggest that the molecular mechanisms of PA will remain research hotspots in the future. International collaboration is also expected to widen and deepen in the field of PA research.